PENGEMBANGAN MEDIA PUZZLE PADA PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG SISWA KELAS IV - Unisha Risna Savira; Urip Tisngati; Mega Isvandiana Purnamasari (DIRASATUL IBTIDAIYAH, 2025)
This study aims to determine and describe the feasibility and effectiveness of mathematical puzzle media on whole number material to improve the arithmetic ability of fourth grade students. The study used the Research Development (RD) method with the ADDIE development model. The research subjects consisted of 1 teacher and 10 fourth grade students of Sukoharjo Public Elementary School. Data collection techniques included observation, interviews, questionnaires, documentation, and arithmetic ability tests. Data analysis conducted included the level of product validity from media and material experts, analysis of teacher and student response questionnaire data on media use, and analysis of product effectiveness test data. The results showed that the puzzle media was declared very valid by media experts with an average assessment of 4.86, and an average of 4.83 by material experts. In addition, the results of the teacher response questionnaire were 100% and the results of the student response questionnaire were 97.33% with a very feasible category. The mathematical puzzle media was said to be quite effective with an average N-Gain score of 0.7 and an effectiveness percentage of 72.8%. Penelitian ini bertujuan untuk mengetahui serta mendeskripsikan timgkat kelayakan dan keefektivitas media puzzle matematika pada materi bilangan cacah untuk meningkatkan kemampuan berhitung siswa kelas IV. Penelitian menggunakan metode Reseacrh Development (RD) dengan model pengembangan ADDIE. Subjek penelitian terdiri 1 guru dan 10 siswa kelas IV SD Negeri Sukoharjo. Teknik pengumpulan data meliputi observasi, wawancara, angket, dokumentasi, dan tes kemampuan berhitung. Analisis data yang dilakukan meliputi tingkat kevalidan produk dari ahli media dan materi, analisa data angket respon guru dan siswa terhadap penggunaan media, serta analisa data uji efektivitas produk. Hasil penelitian menunjukkan bahwa media puzzle dinyatakan sangat valid oleh ahli media dengan rata-rata penilaian adalah 4,86, dan rata-rata 4,83 oleh ahli materi. Selain itu, hasil angket respon guru sebesar 100% dan hasil angket respon siswa sebesar 97,33% dengan kategori sangat layak. Media puzzle matematika dikatakan cukup efektif dengan rata-rata skor  N-Gain sebesar 0,7 dan presentase efektivitas 72,8%.